2003
DOI: 10.2131/jts.28.149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perinatal Exposure to Flutamide on Sex Hormone Responsiveness in F1 Male Rats

Abstract: -Pregnant rats were administered flutamide (0 and 10 mg/kg, p.o.) from gestation Day 14 to post-parturition Day 3 and effects on responsiveness to androgens (testosterone propionate, TP; dihydrotestosterone, DHT) in male offspring were examined with a Hershberger assay.Male pups of each group were assigned to 6 subgroups as follows: Group 1, castration and euthanized at postnatal Day 46 (PND 46); Group 2, castration + vehicle; Group 3, castration + TP; Group 4, castration + DHT; Group 5, vehicle; Group 6, DHT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
(48 reference statements)
3
9
0
Order By: Relevance
“…In this study, in utero exposure to DEHP and Flu caused an increase in the number of nipples and /or areolae in a dose-dependent manner. Our results are in agreement with the previous reports [22,25].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, in utero exposure to DEHP and Flu caused an increase in the number of nipples and /or areolae in a dose-dependent manner. Our results are in agreement with the previous reports [22,25].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, in utero exposure to DEHP and Flu caused an increase in the number of nipples and /or areolae in a dose-dependent manner. Our results are in agreement with the previous reports [22,25]. We demonstrated in this study that DEHP and Flu interfered with the development of reproductive organs in a dose-dependent manner, in agreement with previous reports [12,26].…”
Section: Discussionsupporting
confidence: 94%
“…Elevated testosterone and estrogen levels in neonates affect structural organization of several brain regions, particularly hypothalamic and hippocampal structures (Gore, 2008; McCarthy et al, 2008; Morris et al, 2004). Experimental manipulations that affect the normal developmental hormone levels results in neural changes that persist in the adult brain (Anderson et al, 2005; Bakker and Baum, 2008; Becu-Villalobos et al, 1997; Breedlove, 1997; Dominguez-Salazar et al, 2002; Houtsmuller et al, 1994; Isgor and Sengelaub, 1998; McCormick et al, 1998; McCormick and Mahoney, 1999; Miyata et al, 2003; Seale et al, 2005; Yang et al, 2004). Our data show that disruption of androgen signaling in neonatal male 3xTg-AD mice by administration of the androgen receptor antagonist flutamide resulted in elevated Aβ levels in CA1 hippocampus and subiculum.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we assessed how the adult pattern of Aβ pathology is affected by disruption of the normal organizational effects of sex steroid hormones during critical developmental periods. Specifically, we defeminized neonatal female 3xTg-AD mice using transient testosterone treatment (Meek et al, 2006; Isgor and Sengelaub, 2003; Akhmadeev and Kalimullina, 2005) and demasculinized neonatal male 3xTg-AD mice by temporarily blocking testosterone action using the androgen receptor antagonist flutamide (Miyata et al, 2003; Houtsmuller et al, 1994; Meek et al, 2006; Kudwa et al, 2005). Alterations in adult pathology following these neonatal manipulations provide novel insight into the organizational role of sex steroid hormones on AD-related pathology.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has remained controversial whether all the effects, including those on morphology and function, are actually irreversible. There have appeared reports describing effects of perinatal exposure to anti-androgens on subsequent responsiveness to androgens or anti-androgens [13][14][15] . Furthermore, other studies have revealed change of immunohistochemicallydemonstrable androgen receptor (AR) or nuclear AR concentrations in testis or prostate in adulthood after exposure to estrogenic or anti-androgenic compounds perinatally or prenatally 2,7 .…”
Section: Introductionmentioning
confidence: 99%